Formulation and Evaluation of Red Rice Bran (Oryza rufipogon Griff.) Sleeping Mask with HPMC Variation - Sole, Teresa Ayustin Getrisya; Rejeki, Endang Sri; Purnamasari, Nur Aini Dewi (Indonesian Journal of Pharmaceutical Education, 2025)
Red rice bran (Oryza rufipogon Griff.) is rich in natural antioxidants, including flavonoids, phenolics, and anthocyanins, which offer potential benefits for topical skin care. This study aimed to formulate a sleeping mask containing red rice bran extract using Hydroxypropyl Methylcellulose (HPMC) as a gelling agent and to evaluate its physical characteristics and antioxidant activity. Three formulations were prepared with HPMC concentrations of 5%, 7%, and 9%, in addition to positive and negative controls. The extract was obtained by maceration using 40% acetone. Each formulation was evaluated for organoleptic properties, pH, homogeneity, spreadability, adhesiveness, viscosity, and stability, while antioxidant activity was assessed using the ABTS assay. Results showed that the 5% HPMC formula demonstrated optimal physical qualities (pH 6.02 ± 0.03, viscosity 25,253 ± 122.20 cP, spreadability 4.59 ± 0.12 cm, adhesiveness 2.89 ± 0.28 s), remained stable during storage, and exhibited 32% antioxidant inhibition at 60 ppm. This suggests that the red rice bran sleeping mask with 5% HPMC is a promising formulation for further development as a natural antioxidant-based skincare product.